2016
DOI: 10.1080/10376178.2016.1198236
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric testing of a person-centred care scale the Eden Warmth Survey in a long-term care home in New Zealand

Abstract: The 13-item of EWS-R can be considered as a reliable and predictive scale for assessing quality of life and overall satisfaction on people living in long-term care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Scores in the questionnaire range from 43–15 points, with higher scores denoting more scale scores. Yeung et al () reported an acceptable Cronbach's alpha of .77.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores in the questionnaire range from 43–15 points, with higher scores denoting more scale scores. Yeung et al () reported an acceptable Cronbach's alpha of .77.…”
Section: Methodsmentioning
confidence: 99%
“…with higher scores denoting more scale scores. Yeung et al (2016) reported an acceptable Cronbach's alpha of .77.…”
Section: Research Design Study Participants and Settingmentioning
confidence: 97%
“…When compared with other tools designed by researchers, the TM-PCC survey performs moderately well. The internal consistency and percent variance explained were high when compared to other tools [ 15 , 16 , 19 , 21 , 22 , 26 ]. Additionally, the TM-PCC employed Likert-type scales which are simple to construct and easy to complete for staff; however, this style of questioning can be subject to central tendency bias (i.e., where participants avoid extreme response categories) which could make it difficult to monitor improvement in scores over time.…”
Section: Discussionmentioning
confidence: 84%
“…Specifically, White and colleagues (2008) addressed supportive relationships, which focused on friends and family, but did not include the relationships between residents and staff in their Person-Directed Care Measure [ 27 ]. Other tools have incorporated items on the staff–resident relationship [ 20 , 22 , 23 ], further strengthening the importance for inclusion. Table 2 provides an overview of supporting references for the items [ 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation